EFFECT OF REGULATION OF SOURCE-SINK RELATIONSHIP ON GRAIN YIELD AND ITS COMPONENT OF DIFFERENT BREAD WHEAT CULTIVARS - & Kadom, Jaddoa (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2016)
A field trial was conducted at Abu-Ghraib Research Station-Agricultural Research Directorate-Ministry of Agriculture during the growing seasons of 2012-2013 and 2013-2014. The objective was to investigate the effect of source-sink Regulation on grain yield  and its companents of five bread wheat cultivars (Triticum aestivum L.). Randomized complete block design with the arrangement of split-plots with three replicates was used. Bread wheat cultivars (Bohooth-22, IPA 99, Abu-Ghraib-3,Al-Fath and Al-Rasheed) occupied the main plots while treatments of source-sink relationship regulation occupied the sub-plots. They included eight treatments: Con. control (Con.), S1 (removal of lamina of the flag leaf of main stem), S2 (removal of laminas of the leaf  beneath the flag leaf), S3 (removal of both lamina of the leaf  and the leaf under flag leaf), S4 (removal of upper third spikelets),S5 (removal of median third spikelets), S6 (removal of lower third spikelets) and S7 (removal all spikelets from one side of spike) . Characteristics of plant height, flag leaf area, spike length, no of spikelet per spike, spike weight, and grain yield and its components were measured and estimated. Results of the present study indicated the followings:  Cultivar (Bohooth-22) gave the highest 1000 grain weight (35.70 and 35.31 g) the highest grain yield (5.467 and 5.148 t.ha-1) in both seasons, respectively compared with Abu-Ghraib3 and Al-Rasheed cultivars which gave lowest grain yield (4.918,4.364, 4.239 and 4.352 t.ha-1) in both seasons, respectively and then less 1000 grain weight (30.15, 32.66, 32.61 and 32.77 g), in both seasons, respectively. Treatment (Con.) i.e no modification of source-sink relationship gave the highest grain yield (5.93 and 5.66 t.ha-1) in both seasons, respectively. Treatments of regulation source (S1 and S3)gave grain yield (4.909, 4.698, 4.621and 4.356 t.ha-1), respectively while (S5) treatment gave the lowest grain yield (4.203 t.ha-1) in the first season and (4.061 t.ha-1) in the second season. This indicates that sink regulation treatment was the most influencial in reducing grain yield than the source regulation treatment, especially, treatment (S5) in both seasons where the  median third of spikelets had been removed due to the reduction of spike growth rate (3.18 and 2.49 g.day-1) in both seasons compared with the (Con) treatment which gave the highest values of spike growth rate (3.91 and 3.12 g.day-1) in both seasons, respectively which resulted in the reduction of dry matter translocation in the (S5) treatment (1.87 and 1.74 g.day -1) and consequently in the reduction of 1000 grain weight (30.09 and 31.199) compared with (34.99 and 37.12 g) in the (Con.) treatment in both seasons, respectively.